2017
DOI: 10.1080/10717544.2017.1406561
|View full text |Cite|
|
Sign up to set email alerts
|

Recent developments ind-α-tocopheryl polyethylene glycol-succinate-based nanomedicine for cancer therapy

Abstract: Cancer remains an obstacle to be surmounted by humans. As an FDA-approved biocompatible drug excipient, d-α-tocopheryl polyethylene glycol succinate (TPGS) has been widely applied in drug delivery system (DDS). Along with in-depth analyses of TPGS-based DDS, increasingly attractive results have revealed that TPGS is able to act not only as a simple drug carrier but also as an assistant molecule with various bio-functions to improve anticancer efficacy. In this review, recent advances in TPGS-based DDS are summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 110 publications
(146 reference statements)
0
38
0
Order By: Relevance
“…However, the coumarin‐6‐loaded liposomes were internalized via the cellular endocytosis mechanism, which bypassed the P‐gp mediated drug efflux and enhanced the effects of drug . In addition, TPGS‐coated liposomes resulted in higher cellular uptake due to nonspecific absorbability via absorption‐mediated endocytosis and inhibition of P‐gp efflux by TPGS …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the coumarin‐6‐loaded liposomes were internalized via the cellular endocytosis mechanism, which bypassed the P‐gp mediated drug efflux and enhanced the effects of drug . In addition, TPGS‐coated liposomes resulted in higher cellular uptake due to nonspecific absorbability via absorption‐mediated endocytosis and inhibition of P‐gp efflux by TPGS …”
Section: Resultsmentioning
confidence: 99%
“…Drug efflux transporters, such as P‐gp, on the cytomembrane of MDR cancer cells actively pump out drugs, resulting in a reduction in intracellular drug accumulation and a poor therapeutic effect . Recently, it was shown that TPGS effectively inhibited the overexpression of P‐gp . Consequently, TPGS‐conjugated liposomes may also contribute to the inhibition of P‐gp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] As an US FDA-approved biocompatible excipient, TPGS is widely used in nanocarriers for cancer therapy. 16 TPP and TPGS conjugate could combine both advantages and was synthesized for the first time in this study.…”
Section: Introductionmentioning
confidence: 99%